Efikasi Daun Sirih (Piper betle) sebagai Pestisida Nabati untuk Menekan Populasi Serangga Hama pada Cabai Rawit (Capsicum frutescens L.) - Bintang, Gilang Putra; Herlin, Weri; Pakpahan, Tukkot; Zelianty, Shafa Olivia; Arka, Khoirunisya; Aryanti, Riri Mutiara; Indah, Mawar; Jesika, Jesika (Seminar Nasional Lahan Suboptimal, 2024)
Bintang, G. P., Herlin, W., Pakpahan, T., Zelianty, S. O., Arka, K., Aryanti, R.M., Indah, M., Jesika, J. (2024). Effectiveness of betel leaves (Piper betle) as a vegetable pesticide to suppress pests insect populations on cayenne pepper (Capsicum frutescens L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 90–102). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Cayenne pepper (Capsicum fructuscens L.) has a very high potential for cultivation, but the problem of cayenne pepper cultivation is never free from pest disease, so ethane used chemical pesticides because it is considered more effective and efficient. The purpose of this study was to find out the effectiveness of betel leaf weeds as botanical pesticides to suppressed pests in cayenne pepper. The methods used in this study are Group Randomization Design (GRD) with each group consisting of five treatments, namely P1 (control), P2 (50 gr/l), P3 (100 gr/l), P4 (150 gr/l), P5 (200 gr/) and six tests with a total of 30 cayenne pepper. The results of the studied on P5 (200 gr/l) had the highest insect diversity of 1.94, while P1 (control) had the lowest insect diversity of 1,10. The insect diversity found in the study based on observations from 1 to 80 Days After Planting consisted of 11 species covering several orders such as Lepidoptera, Diptera, Coleoptera, Aranae, Hemiptera, and Hymenoptera. The conclusion of this study is that the higher the dose of betel leaf pesticide used, the lower the attack of insect pests with species of aphids (Aphis gossypii), mealybugs (Pseudococcus sp.), flies (Sarcophaga sp.), caterpillars (Syrphidae sp. larvae), spiders (Araneus sp., Neoscona sp., Paidiscura sp., Oxyopes sp.), ants (Tapinoma sp.), ladybugs (Coccinellidae sp. pupa), and butterflies (Agraulis sp. larvae) on cayenne pepper. Thus, the use of botanical pesticides must be used with the appropriate dose in order to suppress the development of insect pest populations on cayenne pepper.